Impacts of Additional Class on Academic Achievement of Public Senior School Student in Ibadan - Taiwo Oluwakayode Saraye, (International Journal of Natural Sciences: Current and Future Research Trends, 2024)
The purpose of this study was to investigate the impacts of additional class on academic achievement of public senior school students, Ibadan, Oyo state, Nigeria. Different studies have established different reports in their findings that additional class enhance students’ academic achievement. Additional class may be considered as one of the ways to cover syllabus and to make up for missing period of teaching. Students who always attend the additional class might have better grasp of the subject matter and likely have an edge over others. The research methods employed were correlational and descriptive survey. Questionnaire was used to collect data for the study. The data were analysis using multiple regressions. The population of all chemistry students that participated in the study was 535. Respondent sample questionnaire was purposively chosen because they are science students. Reliability index through pilot study of the instruments were 0.731, 0.885 and 0.730. The research findings indicated that the composite effects and relative contributions of perception of students to teaching in various forms of additional class and students’ attendance on students’ academic achievement in chemistry were significant. The researcher recommended the implementation of intensive additional class in chemistry senior secondary schools.